Variable Fixation Technology Provides Rigid as Well as Progressive Dynamic Fixation: A Biomechanical Investigation. (21st October 2020) - Frank, A.; Brianza, S.; Plecko, M.; Raschke, M.J.; Wähnert, D.
Abstract : Background: A new locking-screw technology, the Variable Fixation Locking Screw (VFLS; Biomech Innovations), was developed with the aim of promoting secondary fracture-healing. The VFLS features a resorbable sleeve that progressively decreases its mechanical properties and mass during the fracture-healing time. In this study, we investigated whether the VFLS can provide rigid as well as progressive dynamic fixation. Methods: The interfragmentary stability provided by the VFLS was tested in a simulated fracture-gap model and compared with that provided by standard locking or by a combination of both technologies under compression and torsional loading. Tests were performed with an intact sleeve (initial condition) and after its chemical dissolution. An optical measurement system was used to characterize interfragmentary movements. Results: The axial stiffness did not differ significantly among groups in the initial condition. Sleeve resorption significantly decreased construct stiffness. The torsional stiffness of the samples instrumented with the VFLS was lower than that of the control group. The degradation of the sleeve resulted in a significant increase in axial displacement recorded at both the cis and trans cortices. In samples featuring combined technologies, this increase was about 12% to 20% at the trans cortex and about 50% to 60% at the cis cortex. In samples featuring VFLS technology only, this increase was about 20% to 37% at the trans cortex and about 70% to 125% at the cis cortex. Conclusions: The initial stability offered by the VFLS is equivalent to that of standard locking-screw technology. The resorption of the degradable sleeve leads to effective and reproducible fracture-gap dynamization, progressively varying the way the fracture gap is strained and the magnitude of the strain. Clinical Relevance: The VFLS provides rigid and progressive dynamic fixation in vitro. Such variable stability might have beneficial effects in terms of triggering and boosting secondary fracture-healing.